solve for y:
y^2/b^2=1-x^2/a^2
y= +-b(sqrt(1-x^2/a^2))
if you want the form of the equation at end, multiply the right side by a/a
y= +-b/a sqrt(a^2-x^2)
Now verify by putting this into the original equation.
I seriously do not understand anything about this problem Please help.
The equation of an ellipse centered at the origin is
(x^2/a^2) + (y^2/b^2)=1
The area of the upper half of the ellipse can be determined by finding the area between the ellipse and the x-axis (y=O). The total area of the ellipse is twice the area of the upper half.
(a) Solve the equation of the ellipse for y.(You will obtain two solutions,since there are two y values on the ellipse at every x value). Verify that the positive y values are returned by
y=b/a*square root -(x^2)+a^2
Please help me.
1 answer